A prospective study on antibiotic resistance pattern in patients with urinary tract infection - Singh, Swastika Raj; Thomas, Shibi Mary; Ramaiah, Balakeshwa (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Antibiotics are a blessing to the mankind in the realm of medical treatment. Quite contrary to that fact, they may cause risks in medical treatments of patients if these antibiotics are not taken under medical guidelines. In the current scenario it is a huge challenge for selecting appropriate antibacterial agents for the treatment of UTI. This study aims to evaluate the prescription & resistance pattern of antibiotics in patients with urinary tract infection. Methods: A prospective observational study was carried out for a period of 1 year. Data on 100 research participants' reports and the results of their tests for antibiotic resistance were taken from the microbiology department's records, evaluated, and represented as percentages. Observations were made and meticulously recorded. Results: Out of 100 study participants, Escherichia coli was the most common pathogen with a total of (35%) followed by Klebsiella (17%), Enterococcus with (16%). E. coli were highly resistant to Ampicillin (88.6%) and Cefazolin (88.6%), Ceftraixone (85.3%). Klebsiella were highly resistant to Ampicillin (100%) Cefazolin (93.3%), Cefuroxime (85.7%). Enterococcus were highly resistant to Tetracycline (92.9%) Ciprofloxacin (85.7%), Levofloxacin (81.8%). Where, E. coli were highly sensitive to Amikacin, Imipenem, Ertapenam. Klebsiella were highly sensitive to Meropenem, Cefoperazone/Sulbactam, Amikacin. Enterococcus was highly sensitive to Linezolid, Teicoplanin, Vancomycin. Conclusions: Most of the identified bacteria were resistant to several of the popular antibiotics used in clinical settings. Consequently, it is vital to prescribe antibiotics rationally both before and after culture reports.